Parents' perfectionism and its relation to child rearing behaviors - Bratko, Denis; Greblo, Zrinka (2014)
The aim of the study was to investigate the relationship between parents’ perfectionism and self-reported parenting behaviors. The study included 786 parents (417 mothers and 369 fathers) of high school students. Results showed that parents’ positive and negative perfectionism were differently related to specific forms of child rearing practices. Namely, positive perfectionism was positively, while negative perfectionism was negatively related to parental acceptance for both mothers and fathers. Mothers’ and fathers’ negative perfectionism was positively related to parental criticism and permissiveness. In addition, fathers’ positive perfectionism was negatively associated with permissive child rearing practices. After controlling for background variables, parents’ positive and negative perfectionism explained significant amounts of variance in all self-reported parenting dimensions for fathers and significantly accounted for the variance of parental acceptance and criticism for mothers. According to our findings, parents’ perfectionism might have an important role in shaping parenting behaviors.
Projekt MZOS